The influence of non-stationarity of spike signals on decoding performance in intracortical brain-computer interface: a simulation study - Wan, Zijun; Liu, Tengjun; Ran, Xingchen; Liu, Pengfu; Chen, Weidong; Zhang, Shaomin (Frontiers in Computational Neuroscience, 2023)
Intracortical Brain-Computer Interfaces (iBCI) establish a new pathway to restore motor functions in individuals with paralysis by interfacing directly with the brain to translate movement intention into action. However, the development of iBCI applications is hindered by the non-stationarity of neural signals induced by the recording degradation and neuronal property variance. Many iBCI decoders were developed to overcome this non-stationarity, but its effect on decoding performance remains largely unknown, posing a critical challenge for the practical application of iBCI. To improve our understanding on the effect of non-stationarity, we conducted a 2D-cursor simulation study to examine the influence of various types of non-stationarities. Concentrating on spike signal changes in chronic intracortical recording, we used the following three metrics to simulate the non-stationarity: mean firing rate (MFR), number of isolated units (NIU), and neural preferred directions (PDs). MFR and NIU were decreased to simulate the recording degradation while PDs were changed to simulate the neuronal property variance. Performance evaluation based on simulation data was then conducted on three decoders and two different training schemes. Optimal Linear Estimation (OLE), Kalman Filter (KF) and Recurrent Neural Network (RNN) were implemented as decoders and trained using static and retrained schemes. In our evaluation, RNN decoder and retrained scheme showed consistent better performances under small recording degradation. However, the serious signal degradation would cause significant performance to drop eventually. On the other hand, RNN performs significantly better than the other two decoders in decoding simulated non-stationary spike signals, and the retrained scheme maintains the decoders’ high performance when changes are limited to PDs. Our simulation work demonstrates the effects of neural signal non-stationarity on decoding performance and serves as a reference for selecting decoders and training schemes in chronic iBCI. Our result suggests that comparing to KF and OLE, RNN has better or equivalent performance using both training schemes. Performances of decoders under static scheme are influenced by recording degradation and neuronal property variation while decoders under retrained scheme are only influenced by the former one.